Simultaneous enhancements in the mechanical, thermal, and electrical performances of glass‐fiber‐reinforced cyanate ester/epoxy composites with plasma‐functionalized carbon nanotubes at different temperatures. Issue 6 (13th September 2014) - Li, Jingwen; Wu, Zhixiong; Huang, Chuanjun; Tu, Youping; Li, Laifeng
ABSTRACT Woven glass‐fiber‐reinforced cyanate ester/epoxy composites modified with plasma‐functionalized multiwalled carbon nanotubes (MWCNTs) were prepared. The mechanical, thermal, and electrical properties of the composites were investigated at different temperatures. The results show that the interlaminar shear strength, thermal conductivity, and electrical conductivity of the composites at room temperature and the cryogenic temperatures were enhanced simultaneously by the incorporation of MWCNTs, whereas the nonconductive behavior of the composites as electrical insulating materials was not changed. Meanwhile, the reinforcing mechanism was also examined on the basis of the microstructure of the composites. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41418.